Journal descriptor indexing tool for categorizing text according to discipline or semantic type - Humphrey, Susanne M; Lu, Chris J; Rogers, Willie J; Browne, Allen C (AMIA ... Annual Symposium proceedings, 2006)
A JDI (Journal Descriptor Indexing) tool has been developed at NLM that automatically categorizes biomedical text as input, returning a ranked list, with scores between 0-1, of either JDs (Journal Descriptors, corresponding to biomedical disciplines) or STs (UMLS Semantic Types). Possible applications include WSD (Word Sense Disambiguation) and retrieval according to discipline. The Lexical Systems Group plans to distribute an open source JAVA version of this tool.